Pelatihan Pengemasan Produk Sebagai Strategi Pemasaran Ikan Nila Desa Degayu Pekalongan Utara - Meliza, Meliza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Tilapia is a fish cultivation product produced by Degayu Village and has been processed into various types of processed products. Attractive packaging techniques are needed in order to increase the selling value of the processed tilapia products. Therefore, this product packaging training aims to inform and increase the knowledge of the residents of Degayu Village so that they can package their tilapia products in an attractive and hygienic manner. This training is one of the programs of Research Technology and Information (Ristekin) Pekalongan city. This training aims to increase the knowledge of training participants about marketing techniques to increase sales of tilapia products. This training was attended by PKK women in Degayu Village. The method used in this training is the dissemination of product packaging and the use of packaging labels, the second stage is the practice of using impulse sealer machines and packaging labels, the third stage is evaluation. The results of the training showed that as many as 85% of the training participants were able to produce attractive and hygienic packaging of processed tilapia products and equipped with informative labels.